2017
DOI: 10.21614/chirurgia.112.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Adenomas in Adults and Adolescents. Critical Appraisal and Surgical Strategy in 18 Cases

Abstract: RezumatIntroducere: Studiul nostru subliniazã raritatea cazurilor de adenoame paratiroidiene (AP) publicate în literatura medicalã autohtonã, expresia clinicã diferitã în care predominã formele "istorice" ale bolii ca şi dificultãţile şi întârzierile de diagnostic confirmând totodatã chirurgia ca standardul de aur al tratamentului. Pacienţi şi metodã: Sunt analizate retrospectiv demografia, datele clinice, de laborator şi cele imagistice, procedurile chirurgicale şi constatãrile anatomopatologice ca şi rezulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Nine cases of cancer with ADP, including our present case, have been reported 1,[4][5][6][7][8][9] during the past decade (Table 1). This cohort comprised six men and three women with a median age of 51 years (range, 29-72 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine cases of cancer with ADP, including our present case, have been reported 1,[4][5][6][7][8][9] during the past decade (Table 1). This cohort comprised six men and three women with a median age of 51 years (range, 29-72 years).…”
Section: Discussionmentioning
confidence: 99%
“…Most ADP cases are asymptomatic; the malformation is usually found incidentally during abdominal imaging and detailed examination of the abdominal cavity. 7,9 The patients with ADP may present with diabetes mellitus; hyperglycemia is reported in ~50% of patients with ADP, 5 while only one patient had diabetes mellitus. Although patients with ADP may have sporadic cancers, they have accompanying diabetes mellitus or pancreatitis, which may be associated with the occurrence of pancreatic cancer or ampullary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Diaconescu et al . [29] showed that postoperative clinical and humoral outcome was favorable in all patients with parathyroid adenoma. Following parathyroidectomy, which is the definitive treatment for PHPT, PTH levels normalize within 30 h, while the serum calcium concentration reaches its lowest point in about 24–36 h.[30] With the eventual normalization of the serum calcium levels, there is no premature activation of trypsinogen to trypsin in the pancreatic acinar cells, thereby preventing further attacks of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…PA is the most frequent cause of hyperparathyroidism, accounting for 80-85% of cases, which is usually manifested by elevations in serum parathyroid hormone (PTH) and serum calcium levels (1). Bronchogenic cysts are congenital cystic lesions of the bronchus that occur preferentially in the mediastinum and lung.…”
Section: Introductionmentioning
confidence: 99%